Developing a realist theory of psychosocial rehabilitation: the Clubhouse model - Mutschler, Christina (BMC Health Serv Res, 2018)
BACKGROUND: Psychosocial rehabilitation is a service that supports recovery from mental illness by providing opportunities for skill development, self-determination, and social interaction. One type of psychosocial rehabilitation is the Clubhouse model. The purpose of the current project was to create, test, and refine a realist theory of psychosocial rehabilitation at Progress Place, an accredited Clubhouse. METHOD: Realist evaluation is a theory driven evaluation that uncovers contexts, mechanisms, and outcomes, in order to develop a theory as to how a program works. The current study involved two phases, encompassing four steps: Phase 1 included (1) initial theory development and (2) initial theory refinement; and Phase 2 included (3) theory testing and (4) refinement. RESULTS: The data from this two-phase approach identified three demi-regularities of recovery comprised of specific mechanisms and outcomes: the Restorative demi-regularity, the Reaffirming demi-regularity, and the Re-engaging demi-regularity. The theory derived from these demi-regularities suggests that there are various mechanisms that produce outcomes of recovery from the psychosocial rehabilitation perspective, and as such, it is necessary that programs promote a multifaceted, holistic perspective on recovery. CONCLUSIONS: The realist evaluation identified that Progress Place promotes recovery for members. Additional research on the Clubhouse model should be conducted to further validate that the model initiates change and promotes recovery outcomes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12913-018-3265-9) contains supplementary material, which is available to authorized users.